Housing price diffusion pattern of Australia’s state capital cities - Luo, Zhen Qiang; Liu, Chunlu; Picken, David (International Journal of Strategic Property Management, 2010)
The ripple effect of house prices within metropolitan areas has recently been recognised by researchers. However, it is very difficult to formulate and measure this effect using conventional house price theories particularly in consideration of the spatial locations of cities. Based on econometrics principles of the cointegration test and the error correction model, this research develops an innovative approach to quantitatively examine the diffusion patterns of house prices in mega‐cities of a country. Taking Australia’s eight capital cities as an example, the proposed approach is validated in terms of an empirical study. The results show that a 1–1–2–4 diffusion pattern exists within these cities. Sydney is on the top tier with Melbourne in the second; Perth and Adelaide are in the third level and the other four cities lie on the bottom. This research may be applied to predict the regional housing market behavior in a country. First published online: 18 Oct 2010